Electric internet of things security framework and technologies for energy interconnection - Yiying ZHANG; Baoxian ZHOU; Haoyuan PANG; Jinping CAO; Tongjia ZHANG (Dianxin kexue)
Electric internet of things platform is an important support of energy internet digital innovation service, covering all aspects of power system.There are also many new security problems: how to realize the widely trusted interconnection and reliable perception of the power internet of things, how to realize the intelligent defense and security interaction of the power system, and how to solve the data, application and key security of the power information system.These problems are important tasks to be solved in the current power internet of things.Based on the development of energy internet, the security requirements and characteristics of power internet of things were analyzed.On this basis, the security framework and protection ideas of power internet of things were put forward.Then the key security technologies of the power internet of things and its future development direction were summarized and explained.